2002
DOI: 10.1097/00004770-200205000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Adhesion of Endodontic Sealers to Dentin

Abstract: The bond strength of root canal sealers to dentin seems to be an important property for maintaining the integrity of the seal of root-canal fillings. In the few studies published, various assessment methods were used so quantitative comparison is not possible. The purpose of this study was to develop an effective and easily reproducible model and to test it with nine contemporary, commercially available endodontic sealers. After slicing off the coronal 2 mm of extracted third molars, the exposed dentin served … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
108
0
19

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 13 publications
4
108
0
19
Order By: Relevance
“…An ideal endodontic biomaterial should adhere to the cavity walls and resist dislodging forces to help maintain the integrity of the root filling-dentine interface either under static conditions or during function and operative procedures 15,16) . To assess this property in vitro, the push-out test has been shown to be efficient and reliable as the test conditions are comparable with the clinical situation in which the tested materials are placed directly into prepared canals with a natural canal shape and tubule arrangement 16) .…”
Section: Discussionmentioning
confidence: 99%
“…An ideal endodontic biomaterial should adhere to the cavity walls and resist dislodging forces to help maintain the integrity of the root filling-dentine interface either under static conditions or during function and operative procedures 15,16) . To assess this property in vitro, the push-out test has been shown to be efficient and reliable as the test conditions are comparable with the clinical situation in which the tested materials are placed directly into prepared canals with a natural canal shape and tubule arrangement 16) .…”
Section: Discussionmentioning
confidence: 99%
“…8,15 In the present study, the push-out test was used because it has become a widely accepted method for recording the interfacial bond strength of endodontic materials to root dentin, even at low levels. 16 It has been shown that the push-out test produces a more homogenous stress distribution and less variability than the microtensile bond test during dislocation resistance testing to intraradicular dentin.…”
Section: Discussionmentioning
confidence: 99%
“…연구재료 및 방법 . 전통적인 근관충 전 방법으로 gutta percha와 함께 사용된 epoxy resin sealer는 치근 상아질에 대한 미세결합을 갖는 장점 때문에 많이 사용되어 왔다 18,19) . 그러나 epoxy resin sealer는 gutta percha와 접착을 이루지 못하고 상아질과의 결합력 이 충분하지 못하여 gap을 형성하게 되고 그 공간은 근관치 료의 실패를 유발하는 잠재적인 원인이 될 수 있다 20) .…”
Section: ⅰ 서 론unclassified